2005
DOI: 10.1073/pnas.0502006102
|View full text |Cite
|
Sign up to set email alerts
|

Folding events in the 21-30 region of amyloid β-protein (Aβ) studied in silico

Abstract: Oligomeric assemblies of the amyloid ␤-protein (A␤) have been implicated in the pathogenesis of Alzheimer's disease as a primary source of neurotoxicity. Recent in vitro studies have suggested that a 10-residue segment, Ala-21-Ala-30, forms a turn-like structure that nucleates the folding of the full-length A␤. To gain a mechanistic insight, we simulated A␤(21-30) folding by using a discrete molecular dynamics algorithm and a united-atom model incorporating implicit solvent and a variable electrostatic interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
163
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(179 citation statements)
references
References 35 publications
16
163
0
Order By: Relevance
“…Subsequent studies of the Aβ -peptide demonstrated that the C α proton chemical shift in the VGSNKG(24-29) region does not change over a range of temperature, which suggests that the peptide structure surrounding the VGSN (24)(25)(26)(27) region is stable in the temperature range from 5°-35°. 21,22 Simulation studies21,23,24 lent support for the stability of the proposed structure of the LVFFA(17-21) central hydrophobic cluster and VGSN (24)(25)(26)(27) turn regions on the nanosecond time scale. 21 The conservation of the VGSN (24)(25)(26)(27) turn region in the putative β-fibril25 and the "collapsed coil" structures leads to the conjecture that the VGSN (24)(25)(26)(27) may nucleate the formation of Aβ aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent studies of the Aβ -peptide demonstrated that the C α proton chemical shift in the VGSNKG(24-29) region does not change over a range of temperature, which suggests that the peptide structure surrounding the VGSN (24)(25)(26)(27) region is stable in the temperature range from 5°-35°. 21,22 Simulation studies21,23,24 lent support for the stability of the proposed structure of the LVFFA(17-21) central hydrophobic cluster and VGSN (24)(25)(26)(27) turn regions on the nanosecond time scale. 21 The conservation of the VGSN (24)(25)(26)(27) turn region in the putative β-fibril25 and the "collapsed coil" structures leads to the conjecture that the VGSN (24)(25)(26)(27) may nucleate the formation of Aβ aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Kirschner and coworkers12 used theoretical predictors of β-turn propensity13 to show that the region of sequence centered about residue 26 (as well as residue 8) as having high β-turn potential. Limited proteolysis studies14 identified β-turn in the SNKG (26)(27)(28)(29) region of the full length peptide. NMR and CD spectroscopy15 for the full length Aβ-protein and fragments in a trifluoroethanol and water solution to show that the VGSN (24)(25)(26)(27)) region forms stable turn structures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations